2020
DOI: 10.1038/s42003-020-0945-x
|View full text |Cite
|
Sign up to set email alerts
|

Convolutional neural networks explain tuning properties of anterior, but not middle, face-processing areas in macaque inferotemporal cortex

Abstract: Recent computational studies have emphasized layer-wise quantitative similarity between convolutional neural networks (CNNs) and the primate visual ventral stream. However, whether such similarity holds for the face-selective areas, a subsystem of the higher visual cortex, is not clear. Here, we extensively investigate whether CNNs exhibit tuning properties as previously observed in different macaque face areas. While simulating four past experiments on a variety of CNN models, we sought for the model layer th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
12
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
3
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 61 publications
(140 reference statements)
3
12
0
Order By: Relevance
“…As expected, the neurons of this model have no defined spatial organization and thus result in a random selectivity map. We note the existence of class-selective neurons is not guaranteed, but their appearance here is in-line with observations from prior work [38,50,2]. Secondly, we compare our TVAE model (middle) with our re-implementation of the TDANN [38] (right).…”
Section: Methodssupporting
confidence: 80%
“…As expected, the neurons of this model have no defined spatial organization and thus result in a random selectivity map. We note the existence of class-selective neurons is not guaranteed, but their appearance here is in-line with observations from prior work [38,50,2]. Secondly, we compare our TVAE model (middle) with our re-implementation of the TDANN [38] (right).…”
Section: Methodssupporting
confidence: 80%
“…A recent paper found the 2D Morphable Model, a classic model of face representation from computer vision, could explain neural activity in face patches remarkably well (Chang and Tsao, 2017). At the same time, a number of groups have found that activity in deep layers of convolutional neural networks can explain significant variance of neural responses in ventral temporal cortex (Yamins et al, 2014; Kalfas et al, 2017; Yildirim et al, 2020; Schrimpf et al, 2018; Raman and Hosoya, 2020). Here, we extend those results by comparing the efficacy of a large number of different computational models of face representation to account for neural activity in face patch AM.…”
Section: Discussionmentioning
confidence: 99%
“…Here, we sought to overcome these limitations by adopting the underlying theoretical idea (wiring cost minimization), but building upon recent advances in ANN models (1,12,36). Notably, that prior deep ANN modeling work has already qualitatively demonstrated the presence of at least some "face neurons" within model IT (36) and more recent studies have demonstrated the existence of face-selective units in deep ANNs (37)(38)(39). However, the correspondence of face processing in ANNs and the primate ventral stream has not been tested systematically.…”
Section: Category Choicementioning
confidence: 99%